REFLECTIONS ON THE CITY AS A FUNDAMENTAL HUMAN RIGHT (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article aims to understand the city's designs, analyzing its functioning and its role with the fundamental right of man. It is in the city that man develops his skills and benefits for his needs. This is where relationships work. The essential factor of the city is the dignity of the human person, which is also one of the foundations of today's Democratic Rule of Law. In order to ensure the minimum existential for the lives of citizens, this principle implies that the State must outline, design, implement and execute public policies capable of promoting the sustainable development of cities, the appropriate use of land, the social and environmental function of property, guarantee democracy and citizenship. Although the ordinance contains extensive legislation supporting citizens, we encounter many difficulties in its application. We can highlight as the main factor to this obstacle the individualism that prevents the realization of the common good. Other factors such as real estate speculation and the omission of the government may also be held responsible for attacking fundamental rights, starting with urban exclusion in cities. Urban planning is ineffective, and the city is growing in a disorderly fashion, increasing fortified buildings and spatial segregation. The study stands out by demonstrating the current urban reality about the right to the city and all the implications of this situation unfolds. The research is characterized as being theoretical, qualitative and bibliographic and the method of procedure is deductive, drawing on historical, sociological and legal material from books and scientific articles.